Atmospheric sciences with small satellites - Ishaan, Talamudipi Aditya (Nanyang Technological University, 2024)
This project aims to design the smallest, most lightweight, and most cost-effective micro- or nano-satellite missions in a low-earth equatorial orbit with the highest possible impact by leveraging state-of-the-art satellite technology.